Conformal mapping and periodic cubic spline interpolation - Lee Khiy Wei, 1990-; Ali Hassan Mohamed Murid; Fakulti Sains (2014)
Project Paper (Sarjana Muda Sains (Matematik Industri)) - Universiti Teknologi Malaysia, 2014